(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Zakharchuk M. Ye. Philosophical and educational concepts of inclusive education. The author has analyzed the philosophical and educational concepts of inclusive education. She has also defined the role and importance of inclusive education in the culture of a society. There have been considered the views of scientists on the problem and traced the genesis of inclusive education.